2019
DOI: 10.3390/atmos11010019
|View full text |Cite
|
Sign up to set email alerts
|

Moisture Recycling over the Iberian Peninsula: The Impact of 3DVAR Data Assimilation

Abstract: In this paper, we have estimated the spatiotemporal distribution of moisture recycling over the Iberian Peninsula (IP). The recycling ratio was computed from two simulations over the IP using the Weather Research and Forecasting (WRF) model with a horizontal resolution of 15 km spanning the period 2010–2014. The first simulation (WRF N) was nested inside the ERA-Interim with information passed to the domain through the boundaries. The second run (WRF D) is similar to WRF N, but it also includes 3DVAR data assi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 72 publications
(115 reference statements)
2
4
0
Order By: Relevance
“…The bootstrap analysis with resampling supports this result. Additionally, this is also in agreement with previous studies by the authors, whereby these two simulations were validated against in situ or gridded observational datasets of integrated water vapour, precipitation, evaporation, or wind over coastal areas (Ulazia et al, 2017;González-Rojí et al, 2018). Particularly for integrated water vapour, a variable closely related to the parameters analysed in this study, our verification against an independent satellitebased dataset that has not been assimilated (MODIS) showed that this quantity was substantially better simulated across the whole IP for the D simulation (González-Rojí et al, 2018).…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…The bootstrap analysis with resampling supports this result. Additionally, this is also in agreement with previous studies by the authors, whereby these two simulations were validated against in situ or gridded observational datasets of integrated water vapour, precipitation, evaporation, or wind over coastal areas (Ulazia et al, 2017;González-Rojí et al, 2018). Particularly for integrated water vapour, a variable closely related to the parameters analysed in this study, our verification against an independent satellitebased dataset that has not been assimilated (MODIS) showed that this quantity was substantially better simulated across the whole IP for the D simulation (González-Rojí et al, 2018).…”
Section: Discussionsupporting
confidence: 90%
“…A detailed analysis for Barcelona (Fig. S8) shows that there is a substantial underestimation of moisture at lowest levels by the N simulation, something which is consistent with findings in González-Rojí et al (2018) in a verification with independent non-assimilated MODIS-integrated water vapour. This is also observed in Murcia (figure not shown).…”
Section: Resultssupporting
confidence: 83%
See 3 more Smart Citations